Expressão diferencial de mRNA em células de cultivo infectadas ple herpesvírus bovino 5 - Cagnini, Didier Quevedo [UNESP] (2014)
Bovine herpesvirus 5 (BoHV-5) is an Alphaherpesvirus that causes nonsuppurative meningoencephalitis mainly in young cattle. This disease occurs naturally in either outbreaks or isolated cases, and exhibits low morbidity and high lethality. Besides BoHV-5 epidemiology, pathological findings and diagnosis were well known, the molecular interactions between host cell and BoHV-5 are poorly understood. Molecular biology techniques such as quantitative PCR (qPCR) and RNA sequencing (RNA-seq) are important tools to study virus and host cell interactions. In this study we infected MDBK cells and use the extracted mRNA at 0, 6, 12, 18 and 24h post infection (pi) to analyse BoHV-5 (bICP0, UL9 e US4) and host cell gene (GAPDH) expression using qPCR and 1h, 6h and 24h pi in the RNA-seq study. Mock-infected cells were used to control purpouse. The qPCR releveled that the three BoHV-5 genes showed the same expression behavior during the infection and the GAPDH gene were down-regulated in the infected group. At least 900 genes were differentially expressed during BoHV-5 in each moment analysed by RNA-seq. These genes were up- or down-regulated and mainly associated with cell cycle, interleukin production, inflammatory cells chemotaxis, DNA damage and repair, response to virus, apoptosis, oxidation-reduction process, and ubiquitination pathways. The results demonstrate new insights about BoHV-5 and bovine cells interactions and could be a starting point to new researches and to better understand the pathology of this virus